Hip precautions after hip operation (HippityHop): a before and after study evaluating hip precautions following total hip replacement - Lightfoot, Courtney Jane (2019)
Background Total hip replacement (THR) is a common surgical intervention for treating painful osteoarthritis, especially with end-stage joint deterioration. A well-recognised complication of THR surgery is hip dislocation. To reduce the risk of dislocation, patients are often asked to observe ‘hip precautions’ (that is to restrict certain movements) for several weeks post-surgery. Hip precautions are routinely used despite conflicting evidence regarding their efficacy in reducing dislocation, and divergent clinical opinions as to whether they are detrimental or beneficial to patient recovery.